Early conversion to belatacept after renal transplantation. Issue 5 (19th April 2017) - Nair, Vinay; Liriano‐Ward, Luz; Kent, Rebecca; Huprikar, Shirish; Rana, Mena; Florman, Sander S.; Delaney, Veronica B.; Menon, Madhav C.; Sehgal, Vinita; Miko, Leandra; Khaim, Rafael; Benvenisty, Alan; et al.
Abstract: Belatacept is a non‐nephrotoxic immunosuppressive agent, which may make it the ideal agent for patients with delayed or slow graft function on calcineurin inhibitors. There are limited data on conversion of patients to belatacept within 6 months of transplantation. Between January 2012 and December 2015, 16 patients were converted to belatacept for delayed or poor graft function (eGFR<30 mL/min/1.73 m 2, MDRD); three were HIV positive. Conversion protocols were analyzed in patients ≤4 months and 4‐6 months post‐transplantation. Mean serum creatinine levels after belatacept conversion were compared with preconversion levels. Patient survival was 100%, and graft survival was 88%. The mean creatinine fell from 3.9±1.82 mg/dL prebelatacept conversion to 2.1±1.1 mg/dL at 6 months and 1.9±0.47 mg/dL (median 1.8 mg/dL) at 12 months postconversion. There was no significant increased risk of rejection, infection, or malignancy. HIV parameters remained largely stable. Early conversion to belatacept in patients with DGF or slow graft function is safe and efficacious, in a single‐center nonrandomized retrospective analysis.